Circulating neutrophil extracellular traps in cats with hypertrophic cardiomyopathy and cardiogenic arterial thromboembolism. (23rd March 2023) - Li, Ronald H. L.; Fabella, Arianne; Nguyen, Nghi; Kaplan, Joanna L.; Ontiveros, Eric; Stern, Joshua A.
Abstract: Background: Cats with hypertrophic cardiomyopathy (HCM) are at risk of cardiogenic arterial thromboembolism (CATE). Neutrophil extracellular traps (NETs) may be a potential biomarker and therapeutic target for cardiomyopathy in cats. Hypothesis/Objectives: Characterize NETs in cats with HCM or CATE. We hypothesized that circulating NETs assessed in the form of cell‐free DNA (cfDNA) and citrullinated histone H3 (citH3) are increased in cats with HCM and CATE and associated with reported predisposing factors for thrombus formation. Animals: Eighty‐five cats including client‐owned cats with HCM and CATE and staff‐ and student‐owned clinically healthy cats without HCM. Methods: After echocardiographic evaluations, NETs were measured as cfDNA and citH3. Results: Cats with CATE had significant increases in cfDNA (11.2 ng/μL; interquartile range [IQR],  8.1 to 29.6) compared to those without HCM (8.2 ng/μL; IQR,  5.7 to 11.7 μL; P  = .01) and were responsible for 75% to 83% of cases with cfDNA fragments sized 100 to 2000 base pairs. Citrullinated histone 3, detected in 52% of cats with HCM (31.1 ng/mL; IQR, 16.9 to 29.8), was significantly lower than in those with CATE (48.2 ng/mL; IQR, 34.2 to 60.2; P  = .007). The citH3 concentrations correlated significantly with reported risk factors of CATE, such as left atrial auricular velocity. Conclusions and Clinical Importance: Neutrophil extracellualr traps, especially citH3, are increased in cats with HCM and CATE. They may serve as a novel therapeutic target and biomarker of thrombosis in cats with HCM.